Pemeringkatan kriteria pemilihan pelajar matrikulasi ke universiti menggunakan model set kabur / Wan Rosmanira Ismail, Ummul Khair Salma Hj Din and Norngainy Mohd Tawil - Ismail, Wan Rosmanira; Hj Din, Ummul Khair Salma; Mohd Tawil, Norngainy (UPENA, 2004)
The purpose of this research is to obtain an overview of Ministry of Education matriculation students' criteria in their choice of university. Fuzzy Set of Group Decision Making Model and Fuzzy Conjoint Model are used to analyse the data. The results from both models show that the students chose the courses offered by the university as their first criteria followed by the prerequisite outlined by the universities. Their maturity shown when they placed family advice and influence by friends as their two least important criteria when making their selection.